Air pollution exposure is associated with restrictive ventilatory patterns. Issue 4 (4th August 2016) - de Jong, Kim; Vonk, Judith M.; Zijlema, Wilma L.; Stolk, Ronald P.; van der Plaat, Diana A.; Hoek, Gerard; Brunekreef, Bert; Postma, Dirkje S.; Boezen, H. Marike
Exposure to ambient air pollution is associated with a substantial burden of morbidity and mortality worldwide [1]. In a recent paper, Adam et al. [2] showed significantly impaired levels of forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) associated with exposure to the ambient air pollutants nitrogen dioxide (NO2 ) and particles with a 50% cut-off aerodynamic diameter of 10 μm (PM10 ) in 7613 adults included in the European Study of Cohorts for Air Pollution Effects (ESCAPE). Effect estimates for FVC were of similar magnitude (for NO2 ) or larger (for PM10 ) than those for FEV1 . In line with these findings, Forbes et al. [3] showed negative associations of PM10 and NO2 with the level of FEV1 in 40 329 adults included in the Health Survey for England between 1995 and 2001, whereas no significant associations with FEV1 /FVC were observed. In 1997, the Swiss Study on Air Pollution and Lung Disease in Adults (SAPALDIA), including 9651 adults, showed negative associations of ambient air pollutants NO2 and PM10 with both FEV1 and FVC [4]. The effect estimates for FVC were stronger than for FEV1 for various pollutants, and this was consistently the case in most subgroups (according to smoking status and respiratory symptoms). Reduced FVC, with FEV1 being normal or reduced to a lesser degree than FVC, suggests restrictive rather than obstructive lung disease (in which FEV1 specifically is reduced, resulting in a low FEV1 /FVC ratio). Thus, findings from several European studies suggest that restrictive rather than obstructive ventilatory patterns associate with long-term low levels of exposure to ambient air pollution. A study with slightly different findings is the German Study on the influence of Air Pollution on Lung Function, Inflammation and Ageing (SALIA), including 2593 women. This study also found negative associations of NO2 and PM10 exposure with both FEV1 and FVC, yet the effects estimates for FEV1 were stronger than for FVC, and consequently there were small significant negative associations with the FEV1 /FVC ratio [5]. A review article concluded that despite biological plausible mechanisms, there is suggestive, but not conclusive evidence that chronic exposure to air pollution is associated with the prevalence and incidence of chronic obstructive pulmonary disease (COPD), a disease characterised by airway obstruction [6]. Thus far, no studies have focused explicitly on whether air pollution exposure is associated with obstructive or restrictive ventilatory patterns. Exposure to ambient air pollution is associated with restrictive ventilatory patterns http://ow.ly/QWbD30236J1